Efek Ekstrak Etanol Daun Kelor terhadap Kadar Kreatinin Serum dan Superoksida Dismutase Tikus Model 5/6 Subtotal Nefrektomi - Kuncorojati, Raden Alif; Afifaningrum, Haniy Thri; Swastika, Anis; Afifah, Afifah (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
Chronic Kidney Disease (CKD) is still a major problem in the health sector in the world, including in Indonesia. One of the main pathomechanisms in CKD is oxidative stress. Superoxide dismutase (SOD) is an enzyme that plays a role in fighting oxidative stress. Oxidative stress can be overcome with antioxidants both from inside the body and from the outside obtained from natural materials. Moringa leaves (Moringa oleifera L.) have the potential to prevent the progressivity of CKD because of their flavonoid content which has an antioxidant effect. This study aimed to analyze the effect of Moringa leaf ethanol extract (MLEE) on serum creatinine and SOD levels in rat model 5/6 subtotal nephrectomy. This research is an experimental study with a post-test only with a control group design. A total of 30 male white rats were randomly divided into 5 groups. Group A: sham control, B: subtotal nephrectomy, C, D, and E: treatment groups with MLEE of 200, 400, and 800 mg/kg BW, respectively. On the 15th day after the administration of extracts or aqua dest, sham surgery was carried out in group A, and 5/6 of subtotal nephrectomy in groups B, C, D, and E continued to administer extracts and aqua dest until the 21st day. A blood sample is taken on the 22nd day after surgery, checked serum creatinine levels and SOD. Data were analyzed using One-way ANOVA. The results showed that there was a significant difference in the average serum creatinine levels (p